Edified by the Margent: early modern readings of biblical marginalia - Groves, B (Cambridge University Press, 2023)
This article traces the evidence left by early modern readers who marked their Bibles’ annotations—both by taking attentive notice of them and by leaving their own inky traces on them. Among the burgeoning critical interest in both printed and manuscript marginalia there has been little interrogation of the intersection between the two. This article traces the evidence of what the readerly marginalia of biblical annotations can tell us about their readers. It argues that literacy formed and fostered by reading annotated Bibles was likely to be skillful and attuned to issues of interpretation and meaning-making.